Monitoring interval-training responses for swimming using the 3-min all-out exercise test - Courtright, S. P.; Williams, J. L.; Clark, I. E.; Pettitt, R. W.; Dicks, N. D. (International Journal of Exercise Science, 2016)
The purpose of this study was to determine whether the 3-min all-out exercise test (3MT) could be applied to create an off-season high intensity, interval training (HIIT) program to improve performance, specifically critical velocity (CV), in the sport of swimming. We tested a group of competitive female swimmers (age = 19 ± 1 yrs, height = 169 ± 7 cm, body mass = 69 ± 9 kg) to determine their swimming CV and finite energy capacity >CV (D`), and created a four week (2 d·wk-1) personalized interval training program. Participants were divided in to two groups, a 150yd interval group (n =11) and a 250yd interval group (n =6). Each group completed a series of intervals designed to deplete a given percentage of D` at velocities exceeding CV. A 3MT following the training period was administered to assess for any changes in CV, D`, average velocity during the first 150s of the test (V150s) and total distance traveled (D). Both groups improved their CV (+0.04 m·s-1), V150s (+0.03 m·s-1) and D (+8.64 m) (p D` between groups was not observed (p > 0.05). We conclude that HIIT prescriptions based on a 3MT can improve swim performance over a four-week period. Future research on the fidelity of measuring CV and D` using a swimming 3MT is needed to help aid practitioners in interpreting true training adaptations